2021
DOI: 10.3389/fgene.2020.600232
|View full text |Cite
|
Sign up to set email alerts
|

Re-analysis of a Genome-Wide Gene-By-Environment Interaction Study of Case Parent Trios, Adjusted for Population Stratification

Abstract: We investigate the impact of confounding on the results of a genome-wide association analysis by Beaty et al., which identified multiple single nucleotide polymorphisms that appeared to modify the effect of maternal smoking, alcohol consumption, or multivitamin supplementation on risk of cleft palate. The study sample of case-parent trios was primarily of European and East Asian ancestry, and the distribution of all three exposures differed by ancestral group. Such differences raise the possibility that confou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
2
2
Order By: Relevance
“…This lack of compelling biological plausibility, coupled with the striking differences in exposure distributions between the self-reported European and East Asian strata, motivated our G × E analysis that adjusts for population structure. However, our results (Table 6) and those of (Ratnasekera and McNeney, 2021) do not contradict the hypothesis of G × E, but rather suggest that any G × E signal is due to the self-reported European trios. Further data collection aimed at self-reported European trios may provide stronger conclusions regarding the presence of G × E.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…This lack of compelling biological plausibility, coupled with the striking differences in exposure distributions between the self-reported European and East Asian strata, motivated our G × E analysis that adjusts for population structure. However, our results (Table 6) and those of (Ratnasekera and McNeney, 2021) do not contradict the hypothesis of G × E, but rather suggest that any G × E signal is due to the self-reported European trios. Further data collection aimed at self-reported European trios may provide stronger conclusions regarding the presence of G × E.…”
Section: Discussioncontrasting
confidence: 77%
“…If the frequencies of haplotypes spanning causal SNPs also vary by ancestral groups, exposure-related genetic structure may lead to spurious gene-environment interaction. ( Ratnasekera and McNeney, 2021 ). focused on the self-reported Europeans and East Asians in the GENEVA Oral Cleft Study data.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of compelling biological plausibility, coupled with the striking differences in exposure distributions between the self-reported European and East Asian strata, motivated our G × E analysis that adjusts for population structure. However, our results (Table 6) and those of [13] do not contradict the hypothesis of G × E, but rather suggest that any G × E signal is due to the self-reported European trios. Further data collection aimed at self-reported European trios may provide stronger conclusions regarding the presence of G × E.…”
Section: Discussioncontrasting
confidence: 77%
“…If the frequencies of haplotypes spanning causal SNPs also vary by ancestral groups, exposure-related population stratification may lead to spurious gene-environment interaction. [11] focused on the self-reported Europeans and East Asians in the GENEVA Oral Cleft Study data. Applying the approach of [17], they confirmed the gene-environment interaction found by [2], and concluded that the evidence for gene-environment interaction is predominantly from the data of self-reported Europeans.…”
Section: Introductionmentioning
confidence: 99%